Analisis Kelayakan Perumahan Subsidi Pada Kota Lhokseumawe: Studi Kasus Perumahan Palapa Village Dan Griya Putri Grand - Wahyu Rinaldi; Effan Fahrizal; Sisca Olivia; Yenny Novianti (Prodi Arsitektur Universitas Matana, 2023)
The rapid population growth in developing cities is caused by the large number of immigrants who settle and live there. This case also occurred in Lhokseumawe City, the center of district administration, education, economy and trade on the east coast of Aceh. This condition makes housing development a fundamental need for everyone. The government ensures everyone can own and live in a livable, healthy house with low prices. The government is trying to overcome this by building subsidized housing assisted by the developer so that the middle to the lower economic community can still own and live in a house that follows the existing standard provisions so that it can be said to be a livable house. This study aims to determine the suitability of subsidized housing that has been built based on the standard criteria for building healthy simple houses and the provision of facilities and infrastructure. Qualitative descriptive methods are used to observe and analyze objects based on applicable standards, housing health requirements, and technical guidelines for constructing simple healthy houses and SNI for environmental planning in urban housing. The analysis result defines that the research objects (Palapa Housing and Griya Housing) have followed the standard of healthy simple houses, facilities and infrastructure. Several variables are found inappropriate, such as parks, drainage and waste management at Palapa Housing and parks and clean water supply at Griya Housing. Residents should adapt to the lack or non-compliance of these housing standards.